Implementation in Indonesia Innovation in Entrepreneurship: Analyzing E-Commerce Adoption Trends in the Post-COVID-19 Era - Wibowo, M Arief; Ananda, Alvania Arianti Feby; Nurmalasari, Rengganis; Wulandari, Siti Sri; Artanti, Yessy (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2025)
The development of the era, known as the era of globalization, has had a significant impact on the transaction process between sellers and buyers. E-commerce is an important innovation in the world of entrepreneurship that utilizes the internet network as the basis for its development. The use of e-commerce platforms has increased significantly in recent years. The research method used is descriptive based on literature reviews and literature approaches on the phenomenon of e-commerce development entrepreneurship in Indonesia. E-commerce has presented opportunities and challenges for traditional industries. On the one hand, it has opened up new avenues for businesses to reach global audiences, simplify operations, and improve customer experience. On the other hand, traditional companies must face increasing competition, the need to adapt to rapidly changing consumer preferences, and the pressure to integrate digital technology into their operations.